Boerhaave Syndrome, Pneumothorax, and Chylothorax in a Critically Ill Patient with Tuberous Sclerosis Complex - Mohsin Ijaz; Arsalan Rafiq; Sindhaghatta Venkatram; Gilda Diaz-Fuentes (Case Reports in Critical Care)
Tuberous sclerosis complex (TSC) is an autosomal dominant, variably expressed multisystem disease. The predominant pulmonary features of TSC are identical to those of lymphangioleiomyomatosis (LAM). Pneumothorax, multifocal micronodular pneumocyte hyperplasia, and chylothorax are rare complications of TSC. We report a young male with pneumothorax, lung nodules, and chylous effusion who developed empyema thoracis after esophageal rupture. Hospital course was complicated by respiratory failure. Family opted to transfer to hospice care. Chylothorax is a rare complication of TSC with few scattered reports mostly in female patients. Patients with TSC are usually managed by multispecialists and it is important to be aware of the rare pulmonary manifestations of this disease. A male patient with TSC having lung nodules presenting with chylothorax and empyema thoracis from Boerhaave syndrome makes our case unique.